Property Rights, Theft, and Efficiency: The Biblical Waiver of Fines in the Case of Confessed Theft - Eliakim Katz; Jacob Rosenberg (Bar-Ilan University, Department of Economics, 2001)
In this paper we show that costs associated with infractions of property rights, such as theft, can be reduced by imposing lower penal-ties on individuals who admit to such infractions and make restitution. We find that the socially optimal penalty on a confessed thief may be zero (complete amnesty) or even negative – a person may be given a reward for confessing a theft. The benefits of amnesties were apparently recognized in ancient times and they constitute part of Biblical Law. Moreover, such amnesties have also been informally incorporated into modern legal systems, wherein leniency (a form of partial amnesty) is generally shown to individuals who confess their infractions.
Keywords: 330